Lower gastrointestinal bleeding, vomiting and weight stagnation in a well-appearing neonate with neonatal transient eosinophilic gastroenterocolitis - Bernat Servitje-Verdaguer; Clara Comalrena-de-Sobregrau-Martínez; Carmen-María Sánchez-Molina; Joan-Carles Ferreres-Piñas; Núria Torre-Monmany; Diana García-Tirado (American Journal of Perinatology Reports)
This article presents a novel case of neonatal transient eosinophilic gastroenterocolitis, a proposed new entity causing upper and lower digestive symptoms and extensive gastrointestinal eosinophilic infiltration in newborns without a proven active food allergy. The condition’s proposed pathophysiology and relationship to similar conditions, alongside clinical and therapeutic approaches, are also discussed.